2014
DOI: 10.17953/aicr.38.2.lth8l2314u772j47
|View full text |Cite
|
Sign up to set email alerts
|

The Disappearing Turnout Gap between Native Americans and Non-Native Americans

Abstract: Past research has consistently found that American Indians have traditionally turned out to vote at lower rates than do other citizens. Using two separate data sets, we examine this "turnout gap" over the past several decades. We find that not only has Native American turnout increased generally, but that the "gap" between Native Americans and non-Native Americans has declined substantially, and that in recent elections this "gap" has largely disappeared. We then provide a preliminary and tentative examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…That said, we see that many of the socio-economic variables commonly identified in political participation models for the more general population are relevant to the AI/AN population (Min and Savage 2014, Skopek and Garner 2014). For example, being married, having higher education levels, and household size are important predictors of political participation for AI/ANs.…”
Section: Resultsmentioning
confidence: 95%
“…That said, we see that many of the socio-economic variables commonly identified in political participation models for the more general population are relevant to the AI/AN population (Min and Savage 2014, Skopek and Garner 2014). For example, being married, having higher education levels, and household size are important predictors of political participation for AI/ANs.…”
Section: Resultsmentioning
confidence: 95%
“…The available research on Native American political behavior tells us that Native Americans are less likely to register to vote and vote than other racial and ethnic minority groups in the United States (Huyser et al 2017; Peterson 1997). But the turnout gap of Native Americans has declined significantly over time and may depend on electoral cycle (Skopek and Garner 2014). There is some evidence that Native Americans turn out in greater rates during congressional election years, possibly because these elections matter more for local representation (Huyser et al 2017).…”
Section: Native American Political Behaviormentioning
confidence: 99%
“…Finally, similar to other ethnic and racial minorities, American Indians do not vote in national and state elections as often (Peterson ). Despite the historically lower levels of voter turnout, recent research has demonstrated that this traditional voting “gap” has narrowed in recent years to the point where American Indian turnout in presidential elections is statistically indistinguishable from the rest of the citizenry (Skopek and Garner ). Moreover, the Skopek and Garner () study also finds that American Indians were more likely to care which party wins the election, were slightly more interested in the elections, and had higher levels of political information than they had before 1990.…”
Section: Tribal Political Behaviormentioning
confidence: 99%
“…These economic gains combined with shifts in the Republican Party stance on Indian gaming and court rulings that increase the power of state legislatures to regulate the gaming industry could impact the voting behavior of American Indians who benefit from gaming (i.e., those who live in legislative districts that have built and maintain casinos). Moreover, political participation among American Indians has increased significantly over the past several decades, increasing the electoral significance of American Indians in state elections (Skopek and Garner ). We argue that, partly as a result of these trends, American Indians will seek to influence policies at the state level to protect and grow gaming enterprises.…”
mentioning
confidence: 99%